2005
DOI: 10.1353/hpu.2005.0036
|View full text |Cite
|
Sign up to set email alerts
|

The Health Status of HOPE VI Public Housing Residents

Abstract: The purpose of this study is to provide new data on the relationship between housing quality and health status for people in five HOPE VI public housing developments around the country. HOPE VI is a federal program to replace or redevelop some of the poorest quality public housing in the country. A special survey of residents of these developments was conducted while they lived in HOPE VI housing before its redevelopment. Data for these individuals provides a profile of the quality of housing and the health st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 25 publications
2
25
0
2
Order By: Relevance
“…15,16 Furthermore, smart growth developments that enhance local built environment amenities may increase market demand for nearby housing and decrease the availability of affordable housing. 3 Although previous research examined the impact of overcrowding and poor housing conditions on the health of low-income residents of public housing, 17,18 few studies have examined the extent to which publicly subsidized housing for low-income residents is distributed in relation to health-related built environment factors such as neighborhood walkability, transit access, and traffic exposure. Furthermore, the spatial distribution of affordable units and their proximity to these amenities and hazards could vary systematically by whether the requirements and regulations of affordable housing programs seek to incentivize housing developers to provide low-rent units in new residential buildings or to disperse residents by providing them vouchers to obtain subsidized housing in the wider rental market.…”
mentioning
confidence: 99%
“…15,16 Furthermore, smart growth developments that enhance local built environment amenities may increase market demand for nearby housing and decrease the availability of affordable housing. 3 Although previous research examined the impact of overcrowding and poor housing conditions on the health of low-income residents of public housing, 17,18 few studies have examined the extent to which publicly subsidized housing for low-income residents is distributed in relation to health-related built environment factors such as neighborhood walkability, transit access, and traffic exposure. Furthermore, the spatial distribution of affordable units and their proximity to these amenities and hazards could vary systematically by whether the requirements and regulations of affordable housing programs seek to incentivize housing developers to provide low-rent units in new residential buildings or to disperse residents by providing them vouchers to obtain subsidized housing in the wider rental market.…”
mentioning
confidence: 99%
“…In fact, Howell, Harris, and Popkin found that public housing residents have worse health than comparable persons in assisted housing nationally and other poor people, but they could not directly tie housing quality to health outcomes. 16 Another study included a control for the age of the public housing structure as a proxy for the distress and deterioration of the structures and tested whether or not public housing has any beneficial or protective health features for its residents. 17 Fertig and Reingold argue that public housing ought to improve health because money saved on rent and utilities may be available to improve nutrition or access to health care.…”
mentioning
confidence: 99%
“…Yet, the majority of research on relocations, even relocations into low-poverty neighborhoods, has shown little evidence that health improves 4-5 years after relocation. 1,16,[20][21][22][23][24][25][26] However, it should be noted that one Moving to Opportunity Study (MTO) in New York found declines in distress, 27 and another found declines in obesity 20 for adults moving into low-poverty neighborhoods. Nevertheless, because relocating residents into lowpoverty neighborhoods is expensive and is not a requirement of HOPE VI policy, it is unlikely that the improvements found in MTO will be replicated.…”
mentioning
confidence: 99%
“…In summary, as a placed based strategy, HOPE VI has been effective in reclaiming neighborhoods, reducing crime, and improving the environment (Popkin, 2005; Fraser and Nelson, 2007). However, as a people based strategy, HOPE VI could be considered as being less successful for the most vulnerable population.…”
Section: Appraisal Of Hope VImentioning
confidence: 99%
“…(2008) found that mixed income housing promoted neighborhood revitalization but did not meet the needs of lowerincome residents. They found that mixed income housing was successful in "lowering crime, improving economic indicators, and producing quality housing for market-rate and 31 subsidized tenants…Yet, very low income residents faced barriers to self-sufficiency, health and general well-being" (p. 2141).In summary, as a placed based strategy, HOPE VI has been effective in reclaiming neighborhoods, reducing crime, and improving the environment (Popkin, 2005; Fraser and Nelson, 2007). However, as a people based strategy, HOPE VI could be considered as being less successful for the most vulnerable population.…”
mentioning
confidence: 99%